Identification of Subsurface for Grounding Installation System Using Geoelectrical Method: Case Study of Waru Substation, Sidoarjo, East Java - Khoirunida Anisatu Ainun; Rochman Juan Pandu Gya Nur; Bahri Ayi Syaeful (BIO Web of Conferences)
In the substation planning process, a study of subsurface conditions is needed for a good grounding system. Therefore, information on soil resistivity values is needed that can be used as a reference for related parties to carry out development, which is to determine the grounding locations. This research is to identify the recommended and optimal grounding depth point in the case study of Waru Substation, Sidoarjo, East Java. A good soil for grounding installation is to have a resistivity of less than 1 Ohm. In this research, 2D geoelectric method is used to determine the subsurface resistivity value. The configuration used in this measurement uses Wenner-Schlumberger which is a combination of the Schlumberger configuration which has sensitivity to vertical layer changes and the Wenner configuration which is sensitive to horizontal layer changes. In addition, measurements were also made using the Three Point Method to measure the soil resistance value of the research area, then compared with the resistance value measured using the 2D geoelectric method. The output produced in 2D geoelectric measurements is in the form of apparent resistivity values which will then be processed using Least Square inversion to obtain 2D cross-section modeling. The value and 2D resistivity cross section are a reference for interpretation of where the appropriate depth is for grounding installation. The results of the 2D resistivity cross section show that the subsurface layer is water saturated wet clay with a resistivity value of 0 Ωm -2 Ωm and wet clay with a resistivity value of 3 Ωm - 6 Ωm. Optimal grounding installation occurs at 7 meters depth with 0 Ωm -2 Ωm resistivity in moist soil. Grounding electrode measurements that have been installed on switchyard components can validate each other with the results of 2D cross-section interpretation in determining the optimal grounding depth.